P2X7 as a new target for chrysophanol to treat lipopolysaccharide-induced depression in mice. (2nd February 2016) - Zhang, Kai; Liu, Jingyan; You, Xintong; Kong, Ping; Song, Yichen; Cao, Lu; Yang, Song; Wang, Wenbing; Fu, Qiang; Ma, Zhangqiang
Highlights: Chrysophanol inhibited P2X7 in LPS-induced depression. Chrysophanol inhibited NF-кB in LPS-induced depression. Chrysophanol mitigates lipopolysaccharide-induced depression. Abstract: P2X7 receptor is a ligand gated ion channel found peripheral macrophages and microglia in the nervous system. The current study investigated the relationship between the activated P2X7 and depression for the first time. Chrysophanol (Chr) was examined for its protective effects against depression targeting P2X7. Chr (20 mg/kg, 40 mg/kg) and fluoxetine (20 mg/kg) were intragastrically treated once daily for 7 consecutive days. Lipopolysaccharide (LPS, 0.5 mg/kg) was intraperitoneally injected to develop depression model 30 min after drug administration on day 7. Behavioral tests were measured 24 h after LPS injection. Interleukin (IL)-6, IL-1β and tumor necrosis factor (TNF)-α levels in serum and hippocampus were measured by enzyme-linked immunosorbent assay (ELISA). The expressions of P2X7/NF-κB pathway-related proteins were assessed by western blot. The findings showed that Chr remarkably reduced the elevations of IL-6, IL-1β and TNF-α caused by LPS stimulation. The expressions of P2X7, p-IKKα, p-IKKβ, p-IκBα and p-NF-κBp65 were significantly decreased by Chr pretreatment. In addition, immobility time in tail suspension test (TST) and forced swimming test (FST) were reduced by Chr without affecting spontaneous locomotor activity in open filed test (OFT) and the preference for sucrose was also recovered in sucrose preference test (SPT) with Chr preconditioning. Thus, it is reasonable to speculate that Chr might exert antidepressant effect through inhibiting P2X7/NF-κB signaling pathway.